HAIRY PREGNANCY: A RARE CASE OF GESTATIONAL HYPERANDROGENISM - Makhatar, Nur Hidayah Mohd; Rajoo, Subashini (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND The role of testosterone in pregnancy is usually overlooked. Studies have shown that pregnancy can result in physiological elevation of testosterone, as high as 2 to 3 times the upper limit of normal, but this does not result in the virilisation of the mother. We present a rare case of virilisation during pregnancy with a complete resolution of symptoms post-delivery. CASE This is the case of a 27-year-old female referred for increased hair on her limbs and face, requiring her to shave every 1–2 weeks (Ferriman-Gallway 5). In history, she has had irregular menses starting at 18 years old. She is obese, with a pre-pregnancy weight of 84 kg and a BMI of 35 kg/m². She was treated for polycystic ovarian syndrome (PCOS) by the Gynaecology team. Ovarian ultrasound showed no cysts. The hormonal profile revealed an elevated testosterone level of 5.74 nmol/L (NR: <1.67). Other blood investigations were normal. Further investigation for the hyperandrogenism from possible androgen-producing tumour was postponed till post-delivery. However, during the 6-month follow-up post-delivery, she had regularised menses and reduced facial hair, which minimised regular shaving. Her repeat testosterone level taken 4 months post-delivery was 0.49 nmol/L. CONCLUSION Elevated testosterone during pregnancy is a normal physiological response vital for maintaining pregnancy and initiation of parturition. It is caused by the increased production and reduced clearance of testosterone. Excess testosterone during pregnancy does not cause clinical hyperandrogenism as a result of increased SHBG, which binds the androgens, and placental aromatase, which converts excess testosterone to estradiol. However, PCOS can result in a diminished protective effect of the placental aromatase, resulting in clinical hyperandrogenism during pregnancy. Our patient had a pre-pregnancy PCOS diagnosis, which worsened her hyperandrogenism intrapartum. This condition was similar to a few published case reports. The resolution of PCOS symptoms post-delivery can transiently happen due to the stabilisation of hormones postpartum; unfortunately, PCOS symptoms may recur later on.